Mining Town Crisis: Globalization, Labour, and Resistance in Sudbury - Leadbeater, David (Fernwood, 2008)
Sudbury is the largest hardrock mining centre in North America and among the largest in the world. Given the enormous mineral wealth that exists in the Sudbury Basin, one might think that prosperity would abound and that cultural, educational, health and social-welfare institutions would be of the highest order, existing within a well-maintained and attractive physical infrastructure. But this is not the Sudbury that people know. This book explores key aspects of Sudbury’s economic, health and social conditions. It analyzes how globalization and corporate power in a hinterland mining town have impacted on working people, how and why resistance has emerged and why alternative directions are needed. While Sudbury is the focus of this book, the Sudbury experience offers important lessons for other mining and resource communities. --Publisher's description.
Keywords: History / Canada / General; Political Science / Globalization; Political Science / Labor & Industrial Relations